2015
DOI: 10.1155/2015/831059
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine‐1‐Phosphate and Its Receptors: A Mutual Link between Blood Coagulation and Inflammation

Abstract: Sphingosine-1-phosphate (S1P) is a versatile lipid signaling molecule and key regulator in vascular inflammation. S1P is secreted by platelets, monocytes, and vascular endothelial and smooth muscle cells. It binds specifically to a family of G-protein-coupled receptors, S1P receptors 1 to 5, resulting in downstream signaling and numerous cellular effects. S1P modulates cell proliferation and migration, and mediates proinflammatory responses and apoptosis. In the vascular barrier, S1P regulates permeability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 115 publications
(121 reference statements)
2
46
0
Order By: Relevance
“…Measurements of S1P in serum indicate that it circulates at concentrations of 500 to 1000 nM, albeit significantly protein bound and in some circumstances released by platelet activation. Carriers of S1P include albumin and apolipoprotein M; in serum, S1P is important in vascular homeostasis and immune cell response . There are precedents for osteoblast‐derived S1P as potentially protecting cancer proliferation, but at present physiological levels of S1P in bone and regulation of its production in vivo are not well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of S1P in serum indicate that it circulates at concentrations of 500 to 1000 nM, albeit significantly protein bound and in some circumstances released by platelet activation. Carriers of S1P include albumin and apolipoprotein M; in serum, S1P is important in vascular homeostasis and immune cell response . There are precedents for osteoblast‐derived S1P as potentially protecting cancer proliferation, but at present physiological levels of S1P in bone and regulation of its production in vivo are not well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…1). Sphingosine-1 phosphate is produced via two isoforms of sphingosine kinase (SphK), of which SphK2 is predominant in platelets, and then binds to S1P receptors on endothelial cells and smooth muscle cells [86]. …”
Section: Introductionmentioning
confidence: 99%
“…33,41,[43][44][45][46][47] Previous reports indicated that S1P concentrations in the blood fluid ranged between 0.2 and 0.9 lM, which is high, but the levels were lower in tissues (0.5-75 pmol/mg), suggesting that S1P is secreted by cells in blood vessel walls or by blood cells. 24,25 Thus, the high S1P concentrations that we observed in this study might have arisen because of bleeding during the operation. S1P may be present in the bleb in sufficient amounts to trigger the excessive fibrotic responses.…”
Section: Discussionmentioning
confidence: 76%